Kinetic of Aerobic Decomposition Process of Linear Alkylbenzene Sulfonate (LAS) in a Well-Shaped Bioreactor Using Commercial Inoculum - Margono Margono; Sunu Herwi Pranolo; Joko Waluyo; Bregas Siswahjono Tatag Sembodo; Ari Diana Susanti; Prabang Setyono; Irvan Dahlan (Jurnal Rekayasa Kimia & Lingkungan)
Linear alkylbenzene sulfonate (LAS) belongs to a class of surfactants claimed as an environmentally friendly detergent due to its biodegradability. However, the disposal of LAS waste into the waters without prior treatment causes a risk to the ecosystem. These experiments aimed to study the effects of commercial inoculum size EM-4 on the aerobic decomposition process of LAS in a well-shaped bioreactor. These experiments of LAS decomposition were carried out in a batch system aerated by 2.5 L/min for the low and high initial LAS concentrations. The effects of inoculum acclimation were also investigated for the high LAS concentration. The effects of inoculum size were explored at sizes ranging from 5 to 20% v/v, and samples were taken on a regular basis for residual LAS assessment. The first-order kinetic model gave the best fit to the rate of LAS decomposition, with the highest rate coefficient of 10.44 x 10-2 hour-1. This was achieved by using a 20% v/v inoculum for the initial low concentration of LAS, resulting in the highest decomposition efficiency of 89.4% after 24 hours of incubation. The decomposition rate was slower at the high LAS concentrations than at the low concentrations. The inoculum acclimation increased the decomposition rate for the high LAS concentrations. The results of this study show great potential for the bioremediation of LAS detergent waste using commercial inoculum in a well-shaped batch bioreactor.